ISO 9001-2015: Compliance Audit of Quality Control Product Procedures - Ratna Kumala Sari, Riuh; Riadi, Sugeng (PT Aksara Indo Rajawali, 2023)
This research discusses compliance audits with the implementation of quality control Standard Operating Procedures based on ISO 9001:2015 at TEC Indonesia Corporation. The purpose of this study was to determine the level of employee compliance with the analysis based on ISO 9001:2015 in the Quality Control Product section. This research uses qualitative descriptive methods, and data collection is carried out through documentation techniques, document inspection, interviews, and direct observation at the research site. The results of this study stated the level of conformity and compliance with TEC Indonesia's quality control products with a percentage of 78.5% and a non-compliance rate of 21.5%. In this study, the author found three procedure discrepancies: the act of allowing the use, release, or acceptance through concessions by relevant parties and, if possible, by customers; the absence of review of discrepancies in products, including customer complaints; corrective actions within the company; and the absence of re-verification regarding the implementation of control documents as a corrective measure against non-conforming products.